The Effect of Strategic Alliance and Service Quality on Business Performance Mediated by Customer Satisfaction Perception - Iwan Adi Wibawa; Kesi Widjajanti; Paulus Wardoyo (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze the effects of strategic alliances and service quality on business performance, with customer satisfaction serving as a mediating variable. The research focuses on pharmacies located in Tembalang and Pedurungan Districts. The population consisted of pharmacists responsible for pharmacy operations, and a total of 101 respondents were included in the study. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to examine both direct and indirect relationships among the variables. The results show that strategic alliances and service quality have significant positive effects on customer satisfaction. Strategic alliances also have a significant direct effect on business performance. In contrast, service quality does not directly influence business performance but affects it indirectly through customer satisfaction. Furthermore, customer satisfaction plays a significant mediating role in strengthening the relationship between service quality and business performance. These findings indicate that pharmacy businesses can improve performance by developing effective strategic partnerships and consistently enhancing service quality to increase customer satisfaction. Therefore, customer satisfaction represents an important mechanism through which managerial strategies and service improvements contribute to stronger and more sustainable business performance.